Signs of low energy availability in elite male volleyball athletes but no association with risk of bone stress injury and patellar tendinopathy - Sesbreno, E.; Blondin, D. P.; Dziedzic, C.; Sygo, J.; Haman, F.; Leclerc, S.; Brazeau, A.-S-; Mountjoy, M. (European Journal of Sport Science, 2023)
Relative Energy Deficiency in Sport (RED-S) syndrome is associated with undesirable health and performance outcomes. The aetiology of RED-S syndrome is low energy availability (LEA). LEA has been reported in male athletes in various sports, but there is little information in team sports. Therefore, the aims of this study were to assess the point-prevalence of surrogate markers of LEA in elite male volleyball players and examine the association between low and normal total-testosterone (TES) on endocrine markers, resting metabolic rate, bone mineral density (BMD), and history of injury/illness. Using a cross-sectional design, 22 elite male volleyball players underwent anthropometric, dual-energy X-ray absorptiometry (DEXA or DXA) and resting metabolic rate testing, bloodwork, dietary analysis, the three-factor eating questionnaire-R18, injury/illness questionnaire and Victorian Institute of Sport Assessment - patellar tendon questionnaire. The primary finding of this investigation was that 36% of athletes had =2 surrogate markers of LEA. Although fasted insulin was lower and cortisol was higher in players with low-total TES, low BMD, low RMR and various other endocrine markers linked to LEA were not observed. More research is required to define surrogate markers of LEA in male athletes.